2005
DOI: 10.1007/s10557-005-3693-8
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective-Mimetics Reduce Myocardial Infarct Size in Animals Resistant to Ischemic Preconditioning

Abstract: IPC resistance occurs in this canine model of ischemia-reperfusion injury. However, in spite of IPC resistance, hearts can still be pharmacologically protected by direct application of the K(ATP) channel opener bimakalim or the NHE inhibitor EMD 85131.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Numerous triggers have been identified as being able to elicit and reproduce the effects of IPC [21]. The role of K(ATP) channels as mediators of the cardioprotective effects of preconditioning has been based on the observations that potassium channel openers duplicate these effects, whereas potassium channel blockers eliminate them [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous triggers have been identified as being able to elicit and reproduce the effects of IPC [21]. The role of K(ATP) channels as mediators of the cardioprotective effects of preconditioning has been based on the observations that potassium channel openers duplicate these effects, whereas potassium channel blockers eliminate them [22].…”
Section: Discussionmentioning
confidence: 99%
“…Brief episodes of ischemia render the heart more resistant to subsequent ischemia whose mechanism appears to be mainly due to the activation of ATP-sensitive K + [K(ATP)] channels [2]. Some studies [3][4][5][6] offer a better understanding of the features of this protective effect and its molecular mechanisms. Much attention has been focused recently on the role of mitochondrial K(ATP) channels and the permeability transition pore that seem to play a major role in the progression toward irreversible cellular injury [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Infarct size is a standard marker of cell injury following permanent ischemia-reperfusion (9). A majority of cells die in the infarcted myocardium due to increased sarcolemmal permeability, ATP depletion, and loss of Ca 2ϩ homeostasis (33), whereas many cells at the infarct border zone undergo apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Garcia-Dorado and colleagues (76) reported that the activation of the cGMP/PKG pathway is upstream of delayed normalization of intracellular pH upon reperfusion via PKG-dependent inhibition of Na ϩ /H ϩ -exchange. This indicates that the pre-and postconditioning mechanisms differ substantially because the Na ϩ /H ϩ exchange inhibition seems distant from cardioprotection that is induced by ischemic preconditioning (55).…”
Section: Role Of Transient Reperfusion In the Postconditioning Mechanmentioning
confidence: 99%